HUBUNGAN EXPLOSIVE POWER OTOT LENGAN BAHU DENGAN KEMAMPUAN SHOOTING UNDER RING PADA TIM BOLABASKET PUTRA SMAN 6 PEKNBARU - Juita, Ardiah Juita Ardiah; ', Ibrahim; ', Drs.Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACK : This Researchis a correlation study. This research was conducted at the SMAN 6 Pekanbaru men basketball team. Data were obtained and collected by the independent variable tests (explosive power arm shoulder muscles) and test the dependent variable (shooting under ring capability). The data obtained were analyzed using product moment correlation analysis.Explosive relationship Sleeve Shoulder Muscle Power Shooting Capability under Ring with the SMAN 6 Men's Basketball Team Pekanbaru. Problem identification results showed that men's basketball player SMAN 6 Pekanbaru yet under the ring shooting ability not Maximum. It initials due to the lack of the factors associated with the development of these techniques. By therefore then with lifted Research carried problem